2003
DOI: 10.1002/ajpa.10125
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐related shape changes in the fetal craniofacial complex of humans (Homo sapiens) and pigtailed macaques (Macaca nemestrina): A 3D‐CT comparative analysis

Abstract: This study investigates whether macaques and humans possess a common pattern of relative growth during the fetal period. The fetal samples consist of 16 male pigtailed macaques (mean age, 20.5 gestational weeks) and 17 humans (9 males and 8 females; mean age, 29.5 gestational weeks). For each individual, three-dimensional coordinates of 18 landmarks on the skull were collected from three-dimensional computed tomographic (CT) reconstructed images and two-dimensional CT axial slices. Early and late groups were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 72 publications
4
20
2
Order By: Relevance
“…Nevertheless, the findings clearly show that prenatal elongation of the non-hominoid primate anterior cranial base is significantly greater than that of the posterior base. This closely matches results from previous investigations of the same series of fetal macaques (Sirianni and Newell-Morris, 1980;Zumpano and Richtsmeier, 2003). Although there are no comparable studies for Alouatta, there seems no reason to doubt the linear growth differences reported here.…”
Section: Growth Trendssupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, the findings clearly show that prenatal elongation of the non-hominoid primate anterior cranial base is significantly greater than that of the posterior base. This closely matches results from previous investigations of the same series of fetal macaques (Sirianni and Newell-Morris, 1980;Zumpano and Richtsmeier, 2003). Although there are no comparable studies for Alouatta, there seems no reason to doubt the linear growth differences reported here.…”
Section: Growth Trendssupporting
confidence: 92%
“…Unfortunately, there are no previous studies of Alouatta that are directly comparable to this study. However, previous investigations of the same macaque series report that the angulation remains stable throughout fetal life (Lestrel and Moore, 1978;Moore, 1978;Sirianni and Newell-Morris, 1980;Zumpano and Richtsmeier, 2003). The inconsistency between their findings and the retroflexion reported here is a concern, especially since Moore and others examined many of the same individual specimens studied here.…”
Section: Growth Trendscontrasting
confidence: 61%
See 1 more Smart Citation
“…Zumpano and Richtsmeier 15) reported that the lower face change rates after inferior zygomatic-maxillary sutures were larger in fetal pigtail macaque at the asterionasterion using 3D CT images. The sexual dimorphism difference with regard to body weight and canine size in primates is related to the polygyny associated with parental investment and various ecological factors 16) .…”
Section: Discussionmentioning
confidence: 99%
“…118 Although it is quite common to find morphological variation in samples of individuals, 119 recent studies of postnatal shape trajectories in the craniofacial skeleton point to significant differences among both papionin Old World monkeys (macaques, mangabeys, and baboons) 120 and hominins. 121,122 Thus, in addition to the fact that differences between the craniofacial morphology of humans and nonhuman primates are already evident in fetal stages, 123 these studies indicate that variation in the craniofacial morphology of adult forms of primates is due, in part, to differences in the postnatal ontogenetic shape trajectories. 121 Because the paranasal sinuses, when present, are an inherent part of the facial skeleton, it is most likely that different craniofacial growth patterns are responsible for the variation in the degree of paranasal pneumatization among anthropoids.…”
Section: Growth and Developmentmentioning
confidence: 94%